The story of me - Jones, Stanton L. (God's design for sex, 2007)
Lays a spiritual foundation for the child's understanding of his or her sexuality. Develop an appreciation for God's marvelous gift by understanding some of the basics of human reproduction. Discusses the growth of a child inside the mother's body and the birth process.